Paolo Panceri uno scienziato milanese nella Napoli postunitaria - Borrelli, Antonio (Cavoliniana. Monografie della Società dei Naturalisti in Napoli, 2023)
Paolo Panceri (Milan 1836 - Naples 1877) was one of the most appreciated naturalists of his time. Above all, his research on the luminescence of marine animals made him famous throughout the world. When in 1860 he won the competition for the chair of Comparative Anatomy, newly established in Italy, he preferred the University of Naples to those of Pavia and Bologna. In Naples, his "second homeland", he founded the Museum of Comparative Anatomy and helped, although not a Darwinist, Darwin's follower Anton Dohrn to obtain from the Municipality the land of the Royal Villa, on which the building of the Zoological Station would be built and finally inaugurated in 1875. When he died prematurely, his friend and colleague Emilio Cornalia remembered him with these words: «Tall in person, with brown eyes and hair, with a sweet and insinuating speech, with a reserved and modest demeanor, with a smile on his lips, he was one of those nice men who make themselves immediately understood and loved, and who so rarely meet in the human crowd." This volume retraces Panceri's life: his youthful education in Milan, his studies and early research in Pavia, his relationships with Naples, his friendships inside and outside the academic world, his troubled sentimental affairs, the two trips he made to Egypt over the years 1872-1874.